Rate of Cardiotoxicity in Childhood Acute Lymphoblastic Leukemia Treated with Daunorubicin Using Echocardiography and Troponin I - Sultana, Tania; Chowdhury, Tapas; Islam, Farzana; Ara, Umme Nusrat; Kibria, Chowdhury Shamsul Hoque; Jamal, Chowdhury Yakub; Rahman, A T M Atikur; Karim, Anwarul (University Heart Journal, 2023)
Background and Aim: Acute lymphoblastic leukemia (ALL) is the commonest malignancy in childhood. Childhood ALL Survivors have a lifelong increased risk for cardiovascular morbidity and mortality compared to the general population, mainly caused by chemotherapy with daunorubicin. The aim of the study is to detect the rate of daunorubicin induced cardiotoxicity in children with acute lymphoblastic leukemia during induction phase chemotherapy. Meterials & Methods : This prospective observational study was conducted in the department of Pediatric Hematology and Oncology, Bangabandhu Sheikh Mujib Medical University (BSMMU) on 40 newly diagnosed patients of ALL aged between 1 to17.9 years who got daunorubicin during induction. Complete blood count and echocardiography were done and troponin I was measured in all patients before and after completion of induction period. Result: Of the 40 patients, 8 patients (20%) had developed cardiotoxicity evidenced by reduction of left ventricular ejection fraction (LVEF) in echocardiography. Baseline LVEF was 68.80±5.98% which was then reduced to 65.32±7.07% after induction phase of chemotherapy (p=0.023). No significant alteration of troponin I was seen (P= 0.581) between baseline and after completion of induction. Total WBC count and hemoglobin had a significant difference (P<0.05) between baseline and after induction period. Male patients had a greater risk of developing cardiotoxicity than females but statistically was not significant (P=0.643). There was no significant association between age of the patients and cardiotoxicity (P=0.112).Cardiotoxicity was seen higher in patient with initial high WBC count (p=0.039). Echocardiography also reveled increased tendency of mitral regurgitation and left ventricular hypertrophy after induction phase chemotherapy. Conclusion: This study showed the rate of cardiotoxicity was 20% in ALL patients treated with daunorubicin. It also found that LVEF was decreased during therapy.Echocardiography can be used to detect early cardiotoxicity induced by daunorubicin. University Heart Journal 2023; 19(1): 20-25